Draft Eighth Five Year Plan 1990-95 and Annual Plan 1991-92 Scheme Details Volume—II Government of Manipur - Planning Commission (Planning Commission, 1990)
The scheme envisages strengthening of information support to agricultural development Programme for having effective linkage between Extension Agencies and Media Agencies for dev. purposes by improving facilities for pre-editoring units photo/exhibition units, provision of radio/ video unit, provision of data collector unit, press and binding units at the District/Regional Level.
Government of Manipur, Planning Department